Camels - Wilson, R.T. (Technical Centre for Agricultural and Rural Cooperation, 1998)
The topics covered in this guide to camel management include the origins, domestication and distribution of camels, breeds, production systems, physiology, reproduction, nutrition and health. The use of camels, particularly for transport and milk production, are also discussed.